Sistemas de implantação e irrigação por superfície para cultivo de milho em áreas de arroz irrigado - Gollo, Elisa de Almeida (2016)
The implantation system with rised beds and the use of surface irrigation can be important practices to increase efficiency of the drainage process and ensure the proper establishment of culture in the system of rotation, as well as ensuring the expression of the productive potential of maize in irrigated rice areas. In this way, the objectives of this study were: to assess the response of maize grown in irrigated rice areas as agronomic characteristics, yield components and grain yield under different deployment systems and surface irrigation; and evaluate the efficiency of water use by the culture of maize for the irrigated area treatments in different implantation systems. To reach the objectives, two field experiments were conducted during the crop 2014/15 in experimental systematized area of irrigated rice at the Universidade Federal de Santa Maria-RS. The experiment I, consisted of a factorial, conducted in random blocks design with four replications. The factor levels were composed by deployment systems: A1 = with rised beds; A2 = without rised beds; and factor D levels consisting of: D1 = with irrigation; D2 = without irrigation. Already the experiment II was conducted in random blocks design with two treatments: T1 = Irrigation by furrows; T2 = Witness (without irrigation), both in rised beds, with four replicates. Hybrid maize seeds were used AG9045 in both experiments. The results obtained show that use of the implantation system with rised beds provides an increase in agronomic characteristics of growth and maize yield components as well as increased efficiency of water use and increase in grain yield compared to the system without rised beds. The use of irrigation in periods of drought increases the maize yield in irrigated rice areas, regardless of the implantation system used. The combination of the implantation system with rised beds and furrow irrigation provides greater increase in maize yield, compared to the tested systems.